1967
DOI: 10.1172/jci105644
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Hydrogen Ion Transport in Urinary Bladder of Water Turtle*

Abstract: Abstract. The mechanism of acidification by the urinary bladder of the water turtle was studied in an in vitro system which permitted control and measurement of electrical and concentration driving forces. The rate of hydrogen ion secretion was measured by means of a pH stat technique in the absence of exogenous carbon dioxide and bicarbonate.Transport of hydrogen ion into the solution bathing the mucosal surface of the bladder was associated with the appearance of alkali in the serosal compartment. The mean r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
35
0

Year Published

1967
1967
2014
2014

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 89 publications
(37 citation statements)
references
References 15 publications
2
35
0
Order By: Relevance
“…Urinary bladders of adult fresh water turtles, Pseudentys scripta were removed with minimal handling, washed with Ringer's solution and mounted in lucite chambers as described previously (2).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Urinary bladders of adult fresh water turtles, Pseudentys scripta were removed with minimal handling, washed with Ringer's solution and mounted in lucite chambers as described previously (2).…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have demonstrated that the isolated turtle bladder acidifies the solution bathing its mucosal surface by a mechanism of H+ secretion (2)(3)(4), and that in the absence of external C02 the rate of H+ secretion is markedly reduced by the carbonic anhydrase inhibitor, acetazolamide (2,5). Further studies on the role of carbonic anhydrase in acidification by this urinary menmbrane, however, have yielded results that were inconclusive in several respects.…”
Section: Introductionmentioning
confidence: 99%
“…Although these studies were concerned primarily with an examination of coupling between H+ secretion and transport of Na+ or Cl-, it proved useful to identify the ionic flows that contributed to the short-circuit current (SCC). The ions to be considered are the following: (a) Na+, which is transported actively from the mucosal (M) to serosal (S) medium (3,4), (b) Cl-, which is transported actively from M to S under some experimental conditions (5), and (c) H+, which is transported actively into M (2).…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies (1,2) have shown that in the absence of exogenous C02 and HCOi-the isolated bladder of the water turtle acidifies the solution, bathing its urinary surface by the secretion of hydrogen ion. The addition of HCOs-to the (S)1 side of the bladder reduces the net rate of acid secretion by a mechanism of HCOs-transport from the S to the urinary compartment (3).…”
Section: Introductionmentioning
confidence: 99%
“…To measure the rate of alkali entrance into M after the addition of HCOi-to S, the pH stat method was employed (1). Since measurement of the S to M HCOi-flux requires the absence of net H+ secretion, the M solution for each bladder was acidified to the pH at which net-acid secretion was zero (pH range 4.5-52), while the pH of S was adjusted with NaOH to 8.5 in the absence of exogenous C02 and HCOs (4 The production of lactate by the bladders was not measured in the present study in which the deoxygenation periods were short.…”
Section: Introductionmentioning
confidence: 99%